Cardioprotective actions of nitroxyl donor Angeli's salt are preserved in the diabetic heart and vasculature in the face of nitric oxide resistance. (26th April 2022) - Velagic, Anida; Li, Jasmin Chendi; Qin, Cheng Xue; Li, Mandy; Deo, Minh; Marshall, Sarah A.; Anderson, Dovile; Woodman, Owen L.; Horowitz, John D.; Kemp‐Harper, Barbara K.; Ritchie, Rebecca H.
Abstract : Background and Purpose: The risk of fatal cardiovascular events is increased in patients with type 2 diabetes mellitus (T2DM). A major contributor to poor prognosis is impaired nitric oxide (NO) signalling at the level of tissue responsiveness, termed NO resistance. This study aimed to determine if T2DM promotes NO resistance in the heart and vasculature and whether tissue responsiveness to nitroxyl (HNO) is affected. Experimental Approach: At 8 weeks of age, male Sprague–Dawley rats commenced a high‐fat diet. After 2 weeks, the rats received low‐dose streptozotocin (two intraperitoneal injections, 35 mg·kg −1, over two consecutive days) and continued on the same diet. Twelve weeks later, isolated hearts were Langendorff‐perfused to assess responses to the NO donor diethylamine NONOate (DEA/NO) and the HNO donor Angeli's salt. Isolated mesenteric arteries were utilised to measure vascular responsiveness to the NO donors sodium nitroprusside (SNP) and DEA/NO, and the HNO donor Angeli's salt. Key Results: Inotropic, lusitropic and coronary vasodilator responses to DEA/NO were impaired in T2DM hearts, whereas responses to Angeli's salt were preserved or enhanced. Vasorelaxation to Angeli's salt was augmented in T2DM mesenteric arteries, which were hyporesponsive to the relaxant effects of SNP and DEA/NO. Conclusion and Implications: This is the first evidence that inotropic and lusitropic responses are preserved, and NO resistance in the coronary and mesenteric vasculature is circumvented, by the HNO donor Angeli's salt in T2DM. These findings highlight the cardiovascular therapeutic potential of HNO donors, especially in emergencies such as acute ischaemia or heart failure. Abstract :